Calculation of dissipation fields defects rods short-circuited rotor induction motor - Победа, Татьяна Валерьевна (Eastern-European Journal of Enterprise Technologies, 2014)
Despite the long-term production of induction motors with short-circuited rotor, the technology of rotor casting with aluminum is still being improved and worked out. Information on the type of defect, its nature, location in the rod, as well as the frequency of occurrence is valuable when making adjustments to the casting process. The calculation model for the secondary electromagnetic field, caused by the change in the rotor rod parameters and the calculation model for the rotor rod electromagnetic field from the next rod influence are proposed in the paper. Such fields are usually analyzed by finding the vector magnetic potential values, which satisfy the Helmholtz and Laplace’s equations, taking into account boundary conditions. The ratios for determining normal and tangential components of the electromagnetic field strength were obtained in the paper. Their use allows estimating the rotor rod thinning extent, choosing the optimum sensor height, as well as taking into account the influence of the near-located rods on each other. The diagrams, confirming the correctness of the obtained design ratios are given in the paper.